2003
DOI: 10.1637/7008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Lysine Deficiency on the Immune Response to Newcastle Disease Vaccination in Chickens

Abstract: The effect of lysine deficiency on chicken immune function was evaluated using broiler chickens fed a diet with lysine at 67% of the control diet (1.24% lysine). The evaluation of humoral immune function was conducted by measuring the antibody production to a live Newcastle disease virus (NDV) vaccination using the hemagglutination inhibition (HI) test and enzyme-linked immunosorbent assay (ELISA). The cellular immune function was evaluated through the use of cutaneous basophil hypersensitivity test. The antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…The reason behind is because the fact that Lys integral component for protein synthesis, any deficiency of Lys can limits the immune related protein synthesis includes antibodies and cytokines. Chen et al (2003) reported that Lys deficiency negatively affects antibody response f and cell mediated immunity, also showing adverse effects on growth performance (Liao et al 2015). Similar to the current study, Mushtaq et al (2015) fed higher Lys level to the birds and observed reduced mortality, concluding that higher Lys levels in the diets improves livability.…”
Section: Effect Of Dietary Lysine Regimens On Growth Performance and supporting
confidence: 86%
“…The reason behind is because the fact that Lys integral component for protein synthesis, any deficiency of Lys can limits the immune related protein synthesis includes antibodies and cytokines. Chen et al (2003) reported that Lys deficiency negatively affects antibody response f and cell mediated immunity, also showing adverse effects on growth performance (Liao et al 2015). Similar to the current study, Mushtaq et al (2015) fed higher Lys level to the birds and observed reduced mortality, concluding that higher Lys levels in the diets improves livability.…”
Section: Effect Of Dietary Lysine Regimens On Growth Performance and supporting
confidence: 86%
“…Moreover, Pilevar et al (2011) also reported that a dietary ratio of n-6 to n-3 fatty acids at 10 levels increased antibody titer against NDV in pullet chicks, and this ratio in soybean oil was 7.8 (Table 2). Previously reported that feeding broiler chickens by a lysine-deficient diet (lysine is a precursor of L-carnitine biosynthesis) reduced antibody response to NDV vaccination (Chen et al, 2003). On the other hand, carnitine could be effective on the immune system because it has been found to exhibit immunomodulatory effects during in vivo experiments (Kurth et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in chickens and mammalian species have shown that protein or AA deficiencies may reduce the circulating antibodies available to challenge organisms (Shini and Bryden 2005;Wang et al 2006;Peng et al 2007). For example, Chen et al (2003) found that an inadequate intake of dietary Lys reduced antibody responses and cellmediated immunity in chickens. Klasing and Barnes (1988) have shown broiler chick Lys needs to be lower than normal in birds undergoing immunologic stress.…”
Section: Introductionmentioning
confidence: 99%